Research recast(ed): S3E4 - Re-creating beer and mulsum like ancient times with Dr. Matt Gibbs - Leschyshyn, Brooklyn; Smadis, Natalie; Gibbs, Matt (My University, 2023)
On today’s episode, we talk to Dr. Matt Gibbs about his research into ancient alcohol and recreating mulsum in today’s world. Understanding how alcohol played a role in ancient times, we look at the connection between social bonds and preventing mental and physical illness.
Keywords: alcohol; mulsum; ancient history